2012
DOI: 10.1149/1.3700937
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Dependency of Pure-Boron-Layer Chemical-Vapor Depositions

Abstract: The pattern dependency of pure-boron (PureB) layer chemicalvapor depositions (CVD) is studied with respect to the correlation between the deposition rate and features like loading effects, deposition parameters and deposition window sizes. It is shown experimentally that the oxide coverage ratio and the size of windows to the Si on patterned wafers are the main parameters affecting the deposition rate. This is correlated to the gas depletion of the reactant species in the stationary/low-velocity boundary layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…, ( π π π [8] In this equation, the gas phase depletion in the flow direction is represented by the exponential term. The axial distance x 0 at which the concentration at y = h reaches the critical concentration of 0.99C 0 after correction for the linear velocity profile can be extracted as (14): Following ref.…”
Section: Appendix Amentioning
confidence: 99%
See 1 more Smart Citation
“…, ( π π π [8] In this equation, the gas phase depletion in the flow direction is represented by the exponential term. The axial distance x 0 at which the concentration at y = h reaches the critical concentration of 0.99C 0 after correction for the linear velocity profile can be extracted as (14): Following ref.…”
Section: Appendix Amentioning
confidence: 99%
“…The PureB deposition is susceptible to loading effects and strongly depends to the deposition and reactor conditions (8). In order to achieve better control of the deposition and an understanding of the associated kinetics, the deposition mechanism and growth characteristics should be described.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, it has been shown that less than 2-nm-thick layers can be deposited with good reliability and uniformity by a suitable adjustment of deposition parameters such as deposition time, temperature, partial pressures, and flow rates. 8 In this paper, an investigation is presented of the surface reaction mechanisms and activation energies of PureB layer deposition in the temperature range of 350 C to 850 C. At the lower temperatures, the carrier gas has a large influence on the ability to create the first full boron coverage of the Si. Nevertheless, by first creating a full PureB coverage at 700 C, which is smooth and uniform, and then proceeding with the low-temperature depositions, the boron-on-boron activation energies could be determined over the whole temperature range.…”
mentioning
confidence: 99%
“…In references [14] and [15], the pattern dependency and the loading effect of CVD boron deposition are identified as sources of non-uniformity of the boron layer. Since investigating these two effects requires a thickness-monitoring technique, an end-of-line resistance measurement is introduced as a non-destructive, accurate means of monitoring the boron layer uniformity with fine resolution [16].…”
Section: An Analytical Kinetic Model For Boron Cvdmentioning
confidence: 99%